Memories in Stone of a Terraced Landscape in the Andes. Model Stones of the Sondondo Valley, Peru - Aparicio Martinez , Patricia (2025)
The Sondondo valley, located in the department of Ayacucho, is one of the best examples of terraced landscape in this region of the Andes, as it preserves a large extension of andenes and terraces that are still in use today. In addition, this exceptional valley treasures a unique set of carved stone outcrops that represent the agrarian landscape, they are so-called piedras-maqueta. In this contribution, we will review several aspects of the relationship between these carved stone models and the surroundings where they are located. The rocky outcrops where andenes and terraces are profusely carved, as well as the irrigation system through the engravings of canals and qochas, are today the reflection in stone of the memories of this exceptional terraced landscape. In spite of their abandonment or oblivion in the past, their importance has survived in the environment from different symbols, which demonstrates their strong symbolic power. We will explore the memory of these in the local communities and in the present and past territory where they are located.